Gambaran Karakteristik Pasien Diabetes Melitus di Wilayah Kerja Puskesmas Sikumana Kota Kupang - Oktaviana Salome Naba; Apris A. Adu; Indriati A. Tedju Hinga (Universitas Nusa Cendana, 2021)
Diabetes mellitus is a condition of abnormality characterized by the presence of carbohydrate and fat metabolism that does not get enough insulin continuously, and causes acute and chronic complications. The decrease in the rate of development of complications requires the role of health workers in the puskesmas as the first service unit in the primary prevention of diabetes mellitus. The research aims to find out the characteristics of diabetes mellitus patients in the working area of Sikumana Health Center, Kupang City in 2019. This type of research is descriptive research. The research population was all diabetes mellitus patients in the period January-December 2019 which amounted to 484 patients who received services according to standards. Sampling uses quota sampling techniques and all members of the population are studied. The database collected is the medical record data of diabetes mellitus patients in the puskemas. Data processing and analysis is done descriptively. The results showed that the late elderly were the more diabetic (39.90%) and dominated by female gender (56.40%). Most diabetic patients have a basic education level (46.50%) and the work of most patients is housewives (42.40%). The type of diabetes mellitus cases suffered, most of which are old cases (85.30%). It is expected on the part of the management of non-communicable diseases in the puskesmas to make efforts to improve patient knowledge through the provision of health information periodically with diverse topics related to diabetes mellitus prevention and control measures.